Promoter region single nucleotide polymorphism of siglec-8 gene associates with susceptibility to allergic asthma - Sajay-Asbaghi, Mohammad; Sadeghi-shabestrai, Mahnaz; Monfaredan, Amir; Seyfizadeh, Narges; Razavi, Alireza; Kazemi, Tohid (Personalized medicine, 2020)
Aim: Siglec-8 is exclusively expressed on mast cells, eosinophils and basophils. Possible association of six siglec-8 single nucleotide polymorphisms (SNPs) with susceptibility to allergic asthma in the Azeri population of Iran was investigated in this study. Materials & methods: A total of 194 patients and 190 normal subjects were enrolled. PCR single strand conformation polymorphism (PCR-SSCP) was used to determine the genotypes of the studied SNPs. Results: The rs36498 showed significant association with allergic asthma (odds ratio [OR]: 0.65; p = 0.022) and the T allele was found as a protective allele (OR: 0.61; p = 0.008). Also, eosinophil count in the CC genotype was significantly higher than that in the other genotypes (p = 0.026). Conclusion: The rs36498 is thought to influence the expression level of siglec-8. Siglec-8 could be a potential therapeutic target for allergic asthma.
Gesehen am 05.10.2020